2011
DOI: 10.1177/0891241611408307
|View full text |Cite
|
Sign up to set email alerts
|

Street Codes as Formula Stories: How Inmates Recount Violence

Abstract: Recent developments in the study of narratives suggest that people can construct identity by referencing acculturated stories (i.e., formula stories) and often do so when explaining untoward behavior. Formula stories connect one’s personal identity with generally accepted subcultural identities and the narratives associated with them. In light of this, it becomes clear that cultural codes (e.g., the code of the streets) provide structured storylines. Using data from semistructured interviews with 118 violent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 48 publications
1
48
0
Order By: Relevance
“…Jacobs (2004), for example, interviewed street offenders and found that they used threats and violence to convey a reputation of toughness that requires respect and that, if challenged, would result in violent retaliation. A similar finding holds in other studies, including Baron, Kennedy, and Forde's (2001) study of homeless youth and Rich and Grey's (2005) interviews with young Black male victims (see, generally, Courtwright, 1996; see also Brezina et al, 2004;Brookman et al, 2011;Jacobs and Wright, 2006;Stewart, Schreck, and Simons, 2006). Most extant work, however, has involved qualitative accounts that have not empirically linked prior beliefs to subsequent behavior or, of particular importance for this study, examined the potential effect of the street code on inmate violence.…”
Section: Code Of the Streetsupporting
confidence: 80%
See 2 more Smart Citations
“…Jacobs (2004), for example, interviewed street offenders and found that they used threats and violence to convey a reputation of toughness that requires respect and that, if challenged, would result in violent retaliation. A similar finding holds in other studies, including Baron, Kennedy, and Forde's (2001) study of homeless youth and Rich and Grey's (2005) interviews with young Black male victims (see, generally, Courtwright, 1996; see also Brezina et al, 2004;Brookman et al, 2011;Jacobs and Wright, 2006;Stewart, Schreck, and Simons, 2006). Most extant work, however, has involved qualitative accounts that have not empirically linked prior beliefs to subsequent behavior or, of particular importance for this study, examined the potential effect of the street code on inmate violence.…”
Section: Code Of the Streetsupporting
confidence: 80%
“…A central question that relates to the code of the street is the extent to which adherence to the code is stable or variable over time (Anderson, 1999) and whether particular experiences, such as incarceration, that may occur in prison settings reinforce it. Brookman, Copes, and Hochstetler (2011) showed how inmates may use a street code type of philosophy to make sense of and defend their crimes and, more generally, to create an identity for themselves. A prison setting thus may cement adherence to the street code.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Brookman, Copes, and Hochstetler (2011) put it, the study of self and identity 'provides valuable insights into the links between structural conditions, cultural influences and individual behaviour' (p. 398).…”
Section: A Narrative Frameworkmentioning
confidence: 98%
“…In addition, offenders may seek to portray offences as excusable through referring to sub‐cultural codes (Brookman et al . ) or through comparing themselves favourably to other offenders (Hochstetler et al . 2009).…”
Section: Offender and Illness Narrativesmentioning
confidence: 99%